Biochar and Arbuscular mycorrhizal fungi mediated enhanced drought tolerance in Okra (Abelmoschus esculentus) plant growth, root morphological traits and physiological properties - Jabborova, Dilfuza; Annapurna, Kannepalli; Al-Sadi, Abdullah M.; Alharbi, Sulaiman Ali; Datta, Rahul; Tan, Ali Kee Zuan (King Saud University, 2021)
Drought is a major abiotic factor limiting plant growth and crop production. There is limited information on effect of interaction between biochar and Arbuscular mycorrhizal fungi (AMF) on okra growth, root morphological traits and soil enzyme activities under drought stress. We studied the influence of biochar and AMF on the growth of Okra (Abelmoschus esculentus) in pot experiments in a net house under drought condition. The results showed that the biochar treatment significantly increased plant growth (the plant height by 14.2%, root dry weight by 30.0%) and root morphological traits (projected area by 22.3% and root diameter by 22.7%) under drought stress. In drought stress, biochar treatment significantly enhanced the chlorophyll ‘a’ content by 32.7%, the AMF spore number by 22.8% and the microbial biomass as compared to the control. Plant growth parameters such as plant height, shoot and root dry weights significantly increased by AMF alone, by 16.6%, 21.0% and 40.0% respectively under drought condition. Other plant biometrics viz: the total root length, the root volume, the projected area and root diameter improved significantly with the application of AMF alone by 38.3%, 60.0%,16.8% and 15.9% respectively as compared with control. Compared to the control, AMF treatment alone significantly enhanced the total chlorophyll content by 36.6%, the AMF spore number by 39.0% and the microbial biomass by 29.0% under drought condition. However, the highest values of plant growth parameters (plant height, shoot dry weight, root dry weight) and root morphological traits (the total root length, root volume, projected area, root surface area) were observed in the combined treatment of biochar and AMF treatment viz: 31.9%, 34.2%, 60.0% and 68.6%, 66.6%, 45.5%, 41.8%, respectively compared to the control under drought stress. The nitrogen content, total chlorophyll content and microbial biomass increased over un-inoculated control. The soil enzymes; alkaline phosphatase, dehydrogenase and fluorescein diacetate enzyme activities significantly increased in the combined treatment by 55.8%, 68.7% and 69.5%, respectively as compared to the control under drought stress. We conclude that biochar and AMF together is potentially beneficial for cultivation of okra in drought stress conditions.